The war on cyberterrorism - Marsili, M. (2018)
This article addresses the problem of international law enforcement within the War on Cyberterrorism. Hybrid conflicts have replaced the traditional ones, and new threats have emerged in cyberspace, which has become a virtual battlefield. Cyber threats - cybercrimes, cyberterrorism, cyberwarfare - are a major concern for Western governments, especially for the United States and the North Atlantic Treaty Organization. The international community has begun to consider cyberattacks as a form of terrorism, to which the same measures apply. Because the term "terrorism" is ambiguous and legaly undefined, there is no consensus on a definition of the derivative term "cyberterrorism", which is left to the unilateral interpretations of states. Pretending to consider the cyberspace domain as traditional domains, and claiming to apply IHL for the sole purpose of lawfully using armed forces in contrast to cyberterrorism is a stretch. This paper addresses the question of whether or not current laws of war and international humanitarian law apply to cyber domain, and gives some recommendations on how to tackle this issue.